Perbandingan Analisis Finansial Sistem Kandang Closed House Semi Otomatis dan Otomatis di Peternakan Ayam Dekem Tengah Sawah (Jurnal Agribisnis Indonesia, 2023)
The cage system is one of the supporting factors in broiler chicken farming. In general, closed house cages are the type of cages that are often used by breeders for maintenance because they are considered more efficient for production. Livestock technology in Indonesia continues to develop along with the times. In addition, financial calculations are needed in a business to find out the profit of the business being run. Ayam Dekem Tengah Sawah Farm is a company in the field of raising broiler chickens which was founded in 2016 with a population of 29,000 chickens. The company has 2 (two) closed house cages with different systems, namely semi-automatic and automatic. Using the two cage systems, the owner of the cage does not clearly know the financial benefits that have been implemented. The research was conducted at Ayam Dekem Tengah Sawah Farm, Sumberagung Village, Peterongan District, Jombang Regency. This study aims to determine the differences in closed house cage systems (semi-automatic and automatic) owned by Ayam Dekem Tengah Sawah Farm through financial analysis. The method used is descriptive quantitative. The study was conducted for one period of rearing broiler chickens without special treatment for livestock. The results of this study indicate that the financial analysis of the results of raising broiler chickens using an automatic closed house cage system is superior to the results of raising broiler chickens using a semi-automatic closed house cage system.